Stress Amongst Private University Students in Malaysia - Toh, Seong-Yuen*; Tehseen, Shehnaz*; Mahmoud, Ali B.; Cheok, Jason B.*; Kaur, Ranita* (IGI Global, 2022)
The authors examine the predictive power of individual differences based on the five-factor model(FFM) for stress among undergraduate students in private universities in Malaysia. One hundred thirty-one undergraduate students from three private universities were surveyed. A partial leastsquare structural equation modelling (PLS-SEM) was utilised to analyse the data. The findings indicate that neuroticism and agreeableness positively predict student stress whereas openness to experience, conscientiousness, and extraversion do not exhibit significant or sufficiently sizable predictions of student stress. Notably, female students are found to report higher levels of stress than males. Emotionally unstable students tend to be more vulnerable to forms of stress. Agreeableness signifies the predisposition to be kind and supportive instead of suspicious or adverse towards people. Thus, highly agreeable students may expose themselves to discretionary stress to meet their classmate and tutor expectations. The results are discussed. Further, practical and research implications are provided.